Finite element method calculations of static stress powered by machine learning methods - Harkusha, Vladyslav (National Technical University "Kharkiv Polytechnic Institute", 2025)
Applied mechanics and static analysis specifically have main approach to solve body strain distribution problem called finite element method. However, such approach requires extra input data like ability to create models from engineer and specific programs could solve this task. As a possible way of improvement, we could try to use machine learning technologies and statistical algorithms.
Keywords: finite element method; machine learning; mechanical static analysis